Assessment of antidiabetic, hepatoprotective, and analgesic effects of quinazolinone derivative, (E)-1-Benzoyl-3-((4- (Dimethylamino) Benzylidene) Amino)-2-(4-(Dimethylamino) Phenyl)-2,3 dihydroquinazoline-4(1h)-one, in diabetes induced mice model - Haider Ali; Asif Jan; Gowhar Ali; Syed Shaukat Ali; Abdur Rahim; Ursula Abu Nahla (PLoS ONE, 2026)
Diabetes can cause serious complications such as liver damage and nerve pain. Unfortunately, existing treatment options for these problems often have limited effectiveness and unwanted side effects. To find better therapeutic alternatives with good efficacy and safety profile this study tested a novel quinazolinone derivative, (E)-1-benzoyl-3-((4(dimethylamino)benzylidene)amino)-2-(4-(dimethylamino)phenyl)-2,3 dihydroquinazoline-4(1H)-one , in diabetic mice’s experiencing liver damage and neuropathic pain. Diabetes was induced in mice using alloxan (150 mg/kg). For possible antidiabetic effect, test compound was given in doses of 10 mg/kg and 20 mg/kg. The standard drugs used for comparison was Glibenclamide (5 mg/kg), Tramadol (50 mg/kg) and Diclofenac sodium (50 mg/kg) for pain relief, and Gabapentin (75 mg/kg) for nerve pain. Pain relieving effect was assessed using various test models (e.g., hot plate, writhing, allodynia, and hyperalgesia). Liver function was studied through blood tests and tissue examination. The test compound (at test dose of 20 mg/kg) led to a significant reduction in blood glucose even greater than the reduction seen with glibenclamide (5 mg/kg). Similarly, the test compound significantly reduced pain and showed protective effects on the liver. This new quinazolinone compound was found to be safe and effective in reducing diabetic nerve pain and liver damage in mice. It may offer a better alternative to currently available treatments like gabapentin and glibenclamide.